AD, Volume 24, n° 1 & 2, 1999 - Full Issue - Journal System (Africa Development, 1999)
Contents Class and Ethnicity in the Struggle for Power - The Failure of Democratization in the Congo-Brazzaville Anne Sundberg .......................................1 Citizenship, Alienation and Conflict in Nigeria William O. O. Idowu ..................................31 L'hégémonie ethnique cyclique au nord Cameroun Antoine Socpa ..........................................57 Economic Reform, Political Liberalization and Economic Ethnic Conflict in Kenya Oanda Ogachi .........................................83 The Political Economy of Ethnic Conflicts and Governance in Southern Kaduna, Nigeria: [De]Constructing a Contested Terrain Toure Kazah-Toure ..................................109 Social Rationality and Class Analysis oï National Conflict in Nigeria: A Historiographical Critique Ehimika A. Ifidon ...................................145 Urban Violence in Kenya's Transition to Pluralist Politics, 1982-1992 Godwin Rapando Murunga........................165 Democratic Transition and Political Violence in Nigeria Ebenezer Obadare ..................................199 Policing for Democracy? The Case of the Public Order Police Unit in Durban Monique Marks ....................................221 Index to Africa Development, Vol. XXIII, Nos. 1-4,1998 .....................273